Exploring the factors influencing the intention to clothing and textiles recycling among Chinese college students’: a study based on TPB and VBN - Sun, Ningna; Liu, Dong; Zhang, Jianrui (Frontiers in Psychology, 2024)
Recycling apparel and fabrics is essential for preserving resources and protecting the environment, providing considerable global advantages for ecology and society. This study sought to explore the participation of Chinese college students in the recycling of clothing and fabrics by combining the Theory of Planned Behavior (TPB), the Value-Belief-Norm theory (VBN), self-identity, school education, and perceived policy effectiveness to create a comprehensive model. A total of 1,027 valid samples were obtained through stratified sampling and random sampling, primarily sourced from Eastern China, and analyzed through Structural Equation Modeling (SEM) utilizing AMOS. The results of the research suggested the following: (1) College students’ biospheric values emerged as the most influential factor in predicting their inclination to participate in recycling behavior. (2) VBN (encompassing biospheric and altruistic values) and self-identity significantly contributed to shaping attitude and perceived behavioral control, which in turn impacted individuals’ intention to participate in recycling. (3) School education exerted a stronger moderating influence than perceived policy effectiveness on the relationship between attitude, perceived behavioral control, and intention. The comprehensive model proposed in this study demonstrated superior predictive capability in explaining college students’ willingness to participate in clothing and textiles recycling. It has been proven to be practical and effective. Lastly, schools should promote the practice of clothing and textiles recycling, cultivate good values, and utilize the power of social influence to encourage college students to participate in clothing and textiles recycling. The government should improve relevant laws and regulations, collaborate with academia, and adopt measures like incentives to create a pro-environment atmosphere.